Addition of iptacopan, an oral factor B inhibitor, to eculizumab in patients with paroxysmal nocturnal haemoglobinuria and active haemolysis: an open-label, single-arm, phase 2, proof-of-concept trial. Issue 5 (May 2021) - Risitano, Antonio M; Röth, Alexander; Soret, Juliette; Frieri, Camilla; de Fontbrune, Flore Sicre; Marano, Luana; Alashkar, Ferras; Benajiba, Lina; Marotta, Serena; Rozenberg, Izabela; Milojevic, Julie; End, Peter; et al.
Summary: Background: The haematological benefit of standard-of-care anti-C5 treatment for haemolytic paroxysmal nocturnal haemoglobinuria is limited by residual intravascular haemolysis or emerging C3-mediated extravascular haemolysis. Therefore, the aim of this phase 2 study was to assess the safety, tolerability, pharmacokinetics and pharmacodynamics, and activity of the new complement factor B inhibitor, iptacopan, in patients with paroxysmal nocturnal haemoglobinuria who have active haemolysis despite anti-C5 therapy. Methods: In this multicentre, open-label, single-arm, phase 2 trial, we enrolled adult patients (aged 18–80 years) with paroxysmal nocturnal haemoglobinuria who showed signs of active haemolysis despite receiving eculizumab treatment. Patients were enrolled at Federico II University Hospital (Naples, Italy), Hôpital Saint-Louis (Paris, France), and University Hospital Essen (Essen, Germany). For enrolment, patients were required to show lactate dehydrogenase more than 1·5-times the upper limit of normal and a paroxysmal nocturnal haemoglobinuria type 3 erythrocyte or granulocyte clone size of 10% or greater. Patients with bone marrow failure, on systemic steroid or immunosuppressive drugs, or with severe comorbidities were excluded from the study. Iptacopan was given orally as an add-on therapy at a dose of 200 mg twice daily. The primary endpoint was the effect of iptacopan on the reduction of chronic residual intravascular haemolysis measured as change in lactate dehydrogenase from baseline value to week 13. At 13 weeks, patients could opt into a long-term study extension (ongoing), allowing for modifications of standard treatment. This trial is registered at ClinicialTrials.gov, NCT03439839 . Findings: Between May 31, 2018, and April 9, 2019, ten patients had twice daily 200 mg iptacopan. Iptacopan resulted in marked reduction of lactate dehydrogenase from baseline versus at week 13 (mean 539 IU/L [SD 263] vs 235 IU/L [44], change from baseline −309·2 IU/L [SD 265·5], 90% CI −473·77 to −144·68, p=0·0081), associated with significant improvement of haemoglobin concentrations (mean 97·7 g/L [SD 10·5] vs 129·5 g/L [18·3] change from baseline 31·9 g/L [14·5], 90% CI 23·42–40·28, p<0·0001). All biomarkers of haemolysis improved on iptacopan treatment. Observed haematological benefits were maintained longer than the 13-week study period, throughout the study extension, including seven patients who stopped concomitant standard-of-care treatment and continued iptacopan as monotherapy. There were no deaths or treatment-related serious adverse events during the study period. Of three non-related serious adverse events, two occurred in the same patient (one during run-in and before exposure to iptacopan). Interpretation: Iptacopan at a chronic dose of 200 mg twice daily was well tolerated without any major drug-related safety findings and shows lactate dehydrogenase reduction and haemoglobin normalisation in most patients with paroxysmal nocturnal haemoglobinuria at week 13 and beyond, even in monotherapy. On the basis of these data, iptacopan will be tested as monotherapy in pivotal trials investigating its haematological benefit in a broader paroxysmal nocturnal haemoglobinuria population. Funding: Novartis Institutes for Biomedical Research.